Nonradiative recombination — critical in choosing quantum well number for InGaN/GaN light-emitting diodes - Zhang, Yi Ping (2017)
In this work, InGaN/GaN light-emitting diodes (LEDs) possessing varied quantum well (QW) numbers were systematically investigated both numerically and experimentally. The numerical computations show that with the increased QW number, a reduced electron leakage can be achieved and hence the efficiency droop can be reduced when a constant Shockley-Read-Hall (SRH) nonradiative recombination lifetime is used for all the samples. However, the experimental results indicate that, though the efficiency droop is suppressed, the LED optical power is first improved and then degraded with the increasing QW number. The analysis of the measured external quantum efficiency (EQE) with the increasing current revealed that an increasingly dominant SRH nonradiative recombination is induced with more epitaxial QWs, which can be related to the defect generation due to the strain relaxation, especially when the effective thickness exceeds the critical thickness. These observations were further supported by the carrier lifetime measurement using a pico-second time-resolved photoluminescence (TRPL) system, which allowed for a revised numerical modeling with the different SRH lifetimes considered. This work provides useful guidelines on choosing the critical QW number when designing LED structures.